The Students Perception of The Full Online Learning Quality During The Corona Pandemic - Wahidiyati, Irra (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
Due to the Pandemic of Covid-19, teachers or lecturers must hold a full online teaching-learning process, so they should integrate technology into the teaching learning activities. To engage students in full online learning, Google Classroom, Edmodo, Kahoot, and Quizziz are some online learning platforms that are widely used by English teachers in teaching and learning. There are some video conference applications for doing video calls in the teaching-learning process, they are Zoom and Google Meet. This study focuses on students’ perceptions of the full online learning quality during the corona pandemic. The research involved 50 participants consist of students of the English Education program in the second semester of IAIN Purwokerto. The data were collected through questionnaires, interviews, and observation and were analyzed using the qualitative methods approach. The results of the study indicated that the majority of participants considered did not enjoy the full online learning in English teaching and learning is not effective and efficient in terms of time and phone credit. One of the reasons is the slow-speed internet is one of the difficulties in operating those applications. So, they feel they could not get maximum knowledge and information from their lecturers in full online teaching-learning activities.